The role of iron and black carbon in aerosol light absorption - Y. Derimian; A. Karnieli; Y. J. Kaufman; M. O. Andreae; T. W. Andreae; O. Dubovik; W. Maenhaut; I. Koren (Atmospheric Chemistry and Physics, 2008)
Iron is a major component of atmospheric aerosols, influencing the light absorption ability of mineral dust, and an important micronutrient that affects oceanic biogeochemistry. The regional distribution of the iron concentration in dust is important for climate studies; however, this is difficult to obtain since it requires in-situ aerosol sampling or simulation of complex natural processes. Simultaneous studies of aerosol chemical composition and radiometric measurements of aerosol optical properties, which were performed in the Negev desert of Israel continuously for about eight years, suggest a potential for deriving a relationship between chemical composition and light absorption properties, in particular the spectral single-scattering albedo. The two main data sets of the present study were obtained by a sun/sky radiometer and a stacked filter unit sampler that collects particles in coarse and fine size fractions. Analysis of chemical and optical data showed the presence of mixed dust and pollution aerosol in the study area, although their sources appear to be different. Spectral SSA showed an evident response to increased concentrations of iron, black carbon equivalent matter, and their mixing state. A relationship that relates the spectral SSA, the percentage of iron in total particulate mass, and the pollution components was derived. Results calculated, using this relationship, were compared with measurements from dust episodes in several locations around the globe. The comparison showed reasonable agreement between the calculated and the observed iron concentrations, and supported the validity of the suggested approach for the estimation of iron concentrations in mineral dust.